PERFORMANCE OF FUNDAMENTAL MOTOR SKILLS OF CHILDREN WITH INTELLECTUAL DISABILITIES - Vargas, Leandro Martinez (2015)
This study aims to analyze the performance of fundamental motor skills (locomotor and object control) of children aged 7 to 12 years with intellectual disabilities. 47 students, of both genders, participated in the survey. The children were assessed using the Test of Gross Motor Development - Second Edition (TGMD-2), proposed by Ulrich (2000). Statistical analysis was performed using the Statistical Package for Social Sciences (SPSS), version 20. The results showed that: the children evaluated had delayed motor in relation to the reference population; the difference between chronological age and the estimated motor age for each subtest was significant and; boys showed significantly better performance than the girls on the locomotors and control objects subtests of TGMD-2. We recommend the implementation of an interventional program, aiming to provide a better improvement of the fundamental motor skills of the children and the consequent reduction of motor delay.